ANALISIS INDIKATOR KEMERDEKAAN BELAJAR SISWA DALAM PEMBELAJARAN IPA SMP DI MASA PANDEMI COVID-19 - Arie Nugroho Ramadhan; Ahmad Qosyim (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the learning freedom implementation indicators on mechanisms of heat transfer. This type of research was a case study approach to find out how the teacher's role in the achievement of the learning freedom implementation. The sample in this study, namely 2 science teachers and 27 students of class VII G SMP Negeri 34 Surabaya. The instrument consisted of learning observation sheets, implementations of learning design, and questionnaires. Data obtained by interview, observation, and questionnaire methods were then analyzed descriptively qualitatively. The results of the study showed that: (1) Observation of the learning implementation with the learning freedom concept reached good criteria which showed that the students felt the learning freedom in their learning implementation; (2) The learning implementation carried out by the teacher reached good criteria which showed that most of the learning freedom concepts were implemented; and (3) Questionnaires given to teachers and students show that the learning freedom concept can be achieved for students, while some have not been achieved for teachers. Based on the results the implementation of the concept learning freedom, it can be concluded that this research was very influential on teaching and learning activities.